Pembentukan Identitas Diri Para Pelaku Cover Dance K-Pop di Jakarta - Dwi Sabrina; Lusia Savitri Retno Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2019)
No doubt the development of popular culture is very fast in the world, especially the K-Pop industry. Due to rapid development of K-Pop and more fans, innovations have begun to emerge in showing the love of fans towards K-Pop. One of them is K-Pop cover dance activities. This study discusses